Health and social needs of older adults in slum communities in Ghana: a phenomenological approach used in 2021 - Priscilla Yeye Adumoah Attafuah; Irma HJ Everink; Christa Lohrmann; Aaron Abuosi; Jos MGA Schols (BMC, 2023)
Abstract Slum-dwellers lack several essential amenities (such as water, sanitation, and electricity) which make them more vulnerable than non-slum dwellers. As there is limited to no access to health and social care services in slums, the slum environment is expected to be an even more dangerous environment for older adults, negatively impacting their quality of life (QoL). To provide an overview of the perceived (unmet) health and social care needs and how it affects the QoL, this study aims to explore the self-perceived health and social needs of older adults in urban slums in Ghana. Using a phenomenological approach, 25 semi-structured interviews were conducted between May and June 2021, in the homes of older adults in two slums in Ghana. After coding and analysing the transcripts, five main themes emerged: (a) perception of health; (b) (de)motivators of health service use; (c) perception of social care, (d) social needs, and (e) influence of phenomena on QoL. It appeared that older adults believed that spiritual powers were causing illnesses and influenced their use of formal health services. Other factors such as expired insurance cards and the attitude of healthcare workers served as demotivators for using health services. Perceived health needs were mainly current disease conditions (arthritis, diabetes, hypertension, vision/hearing challenges), challenges with health insurance, the behaviour of some health professionals, the proximity of health facilities, and unnecessary queues at major health facilities. Unmet social needs identified by this study were a sense of neglect by family (need for companionship), requiring assistance with activities of daily living, and the need for financial support. Participants had more health needs than social needs. Health providers do not usually prioritize the care of slum-dwelling older adults. Most participants still have challenges with the National Health Insurance Scheme (NHIS). Their social needs were mainly related to financial difficulties and help with some activities of daily living. Participants expressed that they desired companionship (especially the widowed or divorced ones) and the lack of it made them feel lonely and neglected. Home visits by health professionals to older adults should be encouraged to monitor their health condition and advocate for family members to keep older adults company. Healthcare providers should exhibit positive attitudes and educate older patients on the advantages of formal health services use, as well as the need to seek early treatment as this will influence their QoL to a large extent.